Copywriting Sebagai Pendukung Promosi Berbasis WEB - Waris, Abdul; Rahmawati, Rizka; Anjari, Becik Gati; Murtiyanto, Rizky Kurniawan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Copywriting is an important thing to do to increase the promotion carried out by Fiber to increase the sales of a product or service. The creativity produced in copywriting aims to invite readers to take action from a promotion. With the development of technology, copywriting is now not only presented in physical writing results but also becomes mandatory digitally to keep up with the development of online marketing communication media, such as social media and websites. The creativity of copywriting balanced with up-to-date communication media will be able to spearhead the advertising of a company or organization. The official website, which is generally an information medium, needs promotional writing like social media, in general, to make the official website an effective media utilization, an informative medium, and also a promotional communication medium between the website owner and stakeholders.